Effects of residual feed intake divergence on growth performance, carcass traits, meat quality, and blood biochemical parameters in small-sized meat ducks - H. Bai; Q. Guo; B. Yang; Z. Dong; X. Li; Q. Song; Y. Jiang; Z. Wang; G. Chang; G. Chen (Poultry Science, 2022)
ABSTRACT: Feed efficiency (FE) is a major economic trait of meat duck. This study aimed to evaluate the effects of residual feed intake (RFI) divergence on growth performance, carcass traits, meat quality, and blood biochemical parameters in small-sized meat ducks. A total of 500 healthy 21-day-old male ducks were housed in individual cages until slaughter at 63 d of age. The growth performance was determined for all the ducks. The carcass yield, meat quality, and blood biochemical parameters were determined for the selected 30 high-RFI (HRFI) and 30 low-RFI (LRFI) ducks. In terms of growth performance, the RFI, feed conversion ratio (FCR), and average daily feed intake (ADFI) were found to be significantly lower in the LRFI group (P < 0.01), whereas no differences were observed in the BW and body weight gain (P > 0.05). For slaughter performance, no differences were observed in the carcass traits between the LRFI and HRFI groups (P > 0.05). For meat quality, the shear force of breast muscle was significantly lower in the LRFI group (P < 0.05), while the other meat quality traits of breast and thigh muscles demonstrated no differences (P > 0.05). For blood biochemical parameters, the serum concentrations of triglycerides (TG) and glucose (GLU) were significantly lower in the LRFI group (P < 0.05), while the other parameters showed no differences (P > 0.05). The correlation analysis demonstrated a high positive correlation between RFI, FCR, and ADFI (P < 0.01). The RFI demonstrated a negative effect on the breast muscle and lean meat yields, but a positive effect on the shear force of breast muscle (P < 0.05). Further, the RFI demonstrated a positive effect on the TG and GLU levels (P < 0.05). These results indicate that the selection for low RFI could improve the FE of small-sized meat ducks without affecting the production performance. This study provides valuable insight into the biological processes underlying the variations in FE in small-sized meat ducks.